Nanocellulose-graphene hybrid composites: Fabrication, characterization, applications and environmental impact - Yusuf, J.; Firdaus, A.H.M.; Sapuan, S.M.; Rashid, Umer; Ilyas, R.A.; Hassan, M.R.; Ansari, Mubashshir Ahmad (Elsevier BV, 2024)
Nanocellulose-graphene hybrid composites for high-performance uses have been the focus of recent research. In contrast to graphene, which has great conductivity and mechanical strength, nanocellulose possesses special qualities like renewability and biocompatibility but lacks electrical conductivity. Since graphene-nanocellulose has such promising features, efforts to make flexible electronic composites employing them have accelerated. However, the environmental impacts are needed to be addressed prior to the applications of these hybrid composites. This review article explores environmental aspects for nanocellulose-graphene hybrid composites because of their sustainability, which is a major step in the right direction. The article also emphasizes how these composites have the potential to transform several industries and open the door to a more environmentally friendly future. This paper explores into the most recent developments in nanocellulose-graphene hybrid com posites, highlighting its environmental benefits and adaptability. These composites offer remarkable perfor mance by combining the strength and conductivity of graphene with the mechanical, electrical, and thermal capabilities of nanocellulose.